Best Answer

There is insufficient information to answer this question.

If you mean, what does x equal for: 9 + 6x = 2x

...then the answer is: 9 = 2x - 6x = -4x

...which is equal to: x = -9/4

If you mean, what does x equal for: 9 + 6x + 2x = 0

...then the answer is: 8x = -9

...which is equal to: x = -9/8

Q: What is the answer to 9 plus 6x plus 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

0.2x + 6x - 1 = -9 6.2x = -8 x = -1.2903225806451612903225806451613

8x^3 - 12x^2 + 6x - 9 = (8x^3 - 12x^2) + (6x - 9) = 4x^2(2x - 3) + 3(2x - 3) = (4x^2 + 3)(2x - 3)

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

Related questions

6x + 9 + 2x = 8x + 9

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

6x - 9 + 2x + 1 = 8x -8

5x + x - 6x + 2x = 2x

9+6x = 25-2x 6x+2x = 25-9 8x = 16 x = 2

2x+9=6x-3 Therefore 4x=12 -->x=3

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

2x+92+6x

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

2x+6x=-9 => 8x=-9=> x=-8/9

x + 2x + 6x = 9x

8x-9 -2x plus 11 when solved mathematically is equal to 6x + 2.